The role of hydropower in visions of water resources development for rivers of western Nepal - Pakhtigian, E.L.; Jeuland, M.; Bharati, Luna; Pandey, Vishnu Prasad (Informa UK Limited, 2021)
Water resources can play significant roles in development pathways for water-endowed, low-income countries like Nepal. This article describes three visions for water resource development in the Karnali and Mahakali Basins of Western Nepal: state-led development, demand-driven development and preservation of ecosystem integrity. The analysis calls attention to water use trade-offs, including those resulting from national priorities such as infrastructure-based hydropower and irrigation, from local drinking water demand, and from environmental conservation concerns. While these visions of water resources development do diverge, common trends appear, including acknowledgment of water management’s role in expanding energy access and increasing agricultural productivity.